2015
DOI: 10.21773/boun.29.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Regionalism and ECOWAS Trade Performance: A Gravity Model Approach

Abstract: This paper investigates bilateral trade flows and the level of openness across ECOW-AS-15 nations for the period of 1981-2013 using Poisson pseudo maximum likelihood (PPML), fully modified ordinary least squares (FMOLS) and canonical cointegrating regression (CCR). Comparing the results, the ECOWAS dummy variable was negative and significant in all of the estimation techniques. Financial openness under FMOLS and CCR was negatively significant. Trade openness was found to be negatively significant only under PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…When the similarity in factor endowments or intensities increases by 100 percent, the flows of intermediate exports decline by about 9.5 percent. This finding is in contrast to that of Afolabi et al (2015) who used the difference in per capita income as a proxy for difference in relative factor endowments and obtained a positive and significant coefficient while assessing regionalism and ECOWAS trade performance using a gravity approach. However, it is similar to that of Wang, Wei and Liu (2010) who investigated the determinants of trade flows in OECD countries using gravity panel data models and obtained a negative but significant estimate for the relative factor endowment.…”
contrasting
confidence: 99%
“…When the similarity in factor endowments or intensities increases by 100 percent, the flows of intermediate exports decline by about 9.5 percent. This finding is in contrast to that of Afolabi et al (2015) who used the difference in per capita income as a proxy for difference in relative factor endowments and obtained a positive and significant coefficient while assessing regionalism and ECOWAS trade performance using a gravity approach. However, it is similar to that of Wang, Wei and Liu (2010) who investigated the determinants of trade flows in OECD countries using gravity panel data models and obtained a negative but significant estimate for the relative factor endowment.…”
contrasting
confidence: 99%
“…However, the study did not correct for the endogeneity of the RTAs. Likewise, Luqman et al (2015) investigated the effect of ECOWAS on bilateral trade flows from 1981 to 2013. They used a PPML estimator and found that the ECOWAS dummy variable was negative.…”
Section: Literature Reviewmentioning
confidence: 99%